Studi Literatur : Teori Pembelajaran Kognitivisme dan Konstruktivisme serta Keterkaitannya dengan Model Pembelajaran dalam Penerapan Fisika: Penelitian - Nanda Sawitri Silaen; Nurmaretta Tambunan; Nurul Qadrina; Mariati Purnama Simanjuntak (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This literature study analyzed 20 scientific journals to explore the application of constructivism theory in physics learning. The main focus is identifying how the principles of constructivism are implemented in learning strategies, media development, and learning environments. The results of the analysis show that the constructivist approach, which emphasizes the active role of students in building knowledge through experience, significantly influences the design of physics learning. Learning models such as Problem-Based Learning (PBL) and guided inquiry, which are based on this theory, have proven effective in improving students' understanding of concepts and critical thinking skills. This research highlights the importance of a constructivist approach to creating a more meaningful and relevant physics learning environment.